2020
DOI: 10.1029/2020wr027960
|View full text |Cite
|
Sign up to set email alerts
|

Application of Parameter Screening to Derive Optimal Initial State Adjustments for Streamflow Forecasting

Abstract: Streamflow forecasting is essential in many applications, including the management of hydropower reservoirs and of flood risks. To increase the performance of these hydrologic forecasts, a hydrological model is typically updated with optimal initial model states. These states are usually selected a priori and adjusted to obtain the optimal initial setup. The model states to adjust are generally selected by experts with deep knowledge of the model's behavior. These relationships are rarely documented and formal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Hydrologic models are widely used in applications that are important for society such as flood prediction 1 6 , drought monitoring 7 – 10 , infrastructure design 11 13 , and reservoir management 14 16 . This wide variety of such applications, coupled with the diversity of climatic and physiographic regions and the underlying complexity of hydrologic processes is leading to increasing complexity among these models 17 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrologic models are widely used in applications that are important for society such as flood prediction 1 6 , drought monitoring 7 – 10 , infrastructure design 11 13 , and reservoir management 14 16 . This wide variety of such applications, coupled with the diversity of climatic and physiographic regions and the underlying complexity of hydrologic processes is leading to increasing complexity among these models 17 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The quality of ensemble streamflow forecasts in the U.S. mid-Atlantic region was investigated by Siddique and Mejia [20], and they found that ensemble streamflow forecasts remain skilful for lead times of up to 7 days, and that postprocessing further increased forecast skills across lead times and spatial scales. In Canada, optimal model initial state and input configuration led to reliable short-(days) and long-term (a year) streamflow forecasts [21]. In China, Liu et al [22] demonstrated that ensemble streamflow forecasting systems are skilful up to a lead time of 7 days ahead; however, accuracy deteriorates as the lead time increases.…”
Section: Operational Forecast System and Modelmentioning
confidence: 99%
“…The quality of ensemble streamflow forecasts in the U.S. mid-Atlantic region was investigated by Siddique and Mejia [20], and they found that ensemble streamflow forecasts remain skilful for lead times of up to 7 days, and that postprocessing further increased forecast skills across lead times and spatial scales. In Canada, optimal model initial state and input configuration led to reliable short (days) and long term ( a year) streamflow forecasts [21]. In China, Liu et al [22] demonstrated that ensemble streamflow forecasting system is skilful up to a lead time of 7 days ahead, although accuracy deteriorates as the lead time increases.…”
Section: Introductionmentioning
confidence: 99%